2013
DOI: 10.1001/jamapsychiatry.2013.872
|View full text |Cite
|
Sign up to set email alerts
|

A Multisite, Double-blind, Placebo-Controlled Clinical Trial to Evaluate the Safety and Efficacy of Vigabatrin for Treating Cocaine Dependence

Abstract: Importance: Cocaine dependence is a significant public health problem, yet no validated pharmacological treatment exists. The potent ␥-aminobutyric acid (GABA) ergic medication vigabatrin has previously been shown to be effective in a double-blind single-site study conducted in Mexico.Objective: To evaluate the safety and efficacy of vigabatrin for the treatment of cocaine dependence in a US sample.Design and Setting: Multisite, randomized, doubleblind, placebo-controlled, 12-week clinical trial with follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…However, this high adherence rate was primarily based on data from pill counts and subject self-report. The present study and past reports 10;23;24 indicate that pill counts and self-report greatly overestimate medication adherence relative to PK sampling. Subjects who are financially compensated for their participation in clinical trials may feel compelled to hide medication noncompliance.…”
Section: Discussionmentioning
confidence: 40%
“…However, this high adherence rate was primarily based on data from pill counts and subject self-report. The present study and past reports 10;23;24 indicate that pill counts and self-report greatly overestimate medication adherence relative to PK sampling. Subjects who are financially compensated for their participation in clinical trials may feel compelled to hide medication noncompliance.…”
Section: Discussionmentioning
confidence: 40%
“…Over 1.5 million people in the United States habitually use cocaine (SAMHSA, 2014), but there are no effective treatments for those trying to break the habit (Somoza et al, 2013). This leads to a prolonged cycle of abuse, treatment, and relapse (e.g., Griffin et al, 1989;Vonmoos et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, those receiving GVG were more likely to report abstinence from alcohol (43.5 vs 6.3%), and treatment retention was significantly higher in the GVG group. In a recent multisite, double-blind, placebo-controlled RCT of 186 cocaine-dependent individuals, however, Somoza et al found that there was no statistically significant difference between GVG and placebo in terms of cocaine abstinence or reduction in cocaine-positive urines [113]. The post hoc analysis of GVG urine concentration levels suggested that 40 --60% of patients in the treatment group may not have been adherent with the medication regimen, raising the question of whether the limited efficacy of the medication was due to nonadherence.…”
Section: Vigabatrin and Its Analoguesmentioning
confidence: 98%